Safety and Tolerability of Deferoxamine Mesylate in Patients with Acute Intracerebral Hemorrhage - Selim, Magdy (2011)
BACKGROUND AND PURPOSE: Treatment with the iron chelator, deferoxamine mesylate (DFO), improves neurological recovery in animal models of Intracerebral hemorrhage (ICH). We aimed to evaluate the feasibility, safety, and tolerability of varying dose-tiers of DFO in patients with spontaneous ICH, and to determine the Maximum Tolerated Dose (MTD) to be adopted in future efficacy studies. METHODS: A multicenter, phase-I, dose-finding study using the Continual Reassessment Method. DFO was administered by an intravenous infusion for 3 consecutive days, starting within 18 hours of ICH onset. Subjects underwent repeated clinical assessments through 90 days, and CT neuroimaging pre- and post-drug administration. RESULTS: Twenty subjects were enrolled into 5 dose tiers, starting with 7 mg/kg/day and ending with 62 mg/kg/day as the MTD. Median age was 68 years (range: 50–90); 60% were men; and median GCS and NIHSS scores on admission were 15 (5–15) and 9 (0–39), respectively. ICH location was lobar in 40%, deep in 50%, and brainstem in 10%; intraventricular hemorrhage was present in 15%. DFO was discontinued due to adverse events in 2 subjects (10%). Six subjects (30%) experienced 12 serious adverse events (SAEs), none were drug-related. DFO infusions were associated with mild blood pressure lowering effects. Fifty percent of patients had mRS ≤2 and 39% had mRS 4–6 on day-90; 15% died. CONCLUSIONS: Consecutive daily infusions of DFO after ICH are feasible, well-tolerated, and not associated with excessive SAEs or mortality. Our findings lay the groundwork for future studies to evaluate the efficacy of DFO in ICH.